2015
DOI: 10.21465/rp0022.0004
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stressors, risks and health in the seafaring population

Abstract: According to the latest assessment of the global supply and demand for seafarers (BIMCO/ISF, 2010), worldwide supply of seafarers is estimated to be 1 371 000, i.e., 624 000 officers and 747 000 ratings or crew members. BIM-CO/ISF (2010) show continued positive trends in both demand and supply of seafarers despite the global economic downturn, but it also reflects significant increases in seafarers from some countries, particularly China, India and the Philippines, as well as in several European countries. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 27 publications
1
28
0
2
Order By: Relevance
“…The regression analysis has confirmed the second assumption and it has been found out that the knowledge about the research subject is a more important variable than the sex affiliation. The students at the Faculty of Maritime Studies in Split were involved in the survey because a part of their curriculum refers to health education, provided in the courses in First aid and Medicine for seafarers, as well as due to the risks associated with living separately from their families [2,14,15]. The research results have confirmed the importance of health literacy and continuing education of the young population with the purpose of sex disease prevention, reproductive health care and, consequently, improvement of the demographic image of the nation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regression analysis has confirmed the second assumption and it has been found out that the knowledge about the research subject is a more important variable than the sex affiliation. The students at the Faculty of Maritime Studies in Split were involved in the survey because a part of their curriculum refers to health education, provided in the courses in First aid and Medicine for seafarers, as well as due to the risks associated with living separately from their families [2,14,15]. The research results have confirmed the importance of health literacy and continuing education of the young population with the purpose of sex disease prevention, reproductive health care and, consequently, improvement of the demographic image of the nation.…”
Section: Discussionmentioning
confidence: 99%
“…Seafaring is characterised by specific psycho-social, mental and physical stressors such as long periods away from home, isolation, long working hours, fatigue, lack of shore leave, high levels of work related stress, exposure to toxic and hazardous substances, communicable diseases, impaired treatment options for cardiovascular diseases, and dangers of piracy [1][2][3].…”
mentioning
confidence: 99%
“…Fatigue is often a result of a work-related stress and can depend on the complexity of the work and the number of crew units, the sample proportions p 1 [7]. Shift work, especially night work has been recognized as an important factor in the development of insomnia, as well as other serious diseases such as gastrointestinal and cardiovascular ones [8]. Typical symptoms of stress, such as insomnia, lack of concentration, anxiety, frustration, anger and headache affect the quality of work-related tasks [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fereshteh Baygi et al, Physical health threatening factors of Iranian seafarer health [7]. In some quantitative studies physical health of seafarers with focus on cancer and cardiovascular diseases was assessed [8].…”
mentioning
confidence: 99%